A simulation-based approach to provide insights on Hyperloop network operations. (March 2020) - Rajendran, Suchithra; Harper, Aidan
Abstract: Expected to operate in the forthcoming decade, Hyperloop is a magnetically levitated capsule that aims to transport passengers between metropolitan cities at a very high speed. To the best of the authors' knowledge, this research is the first to study the Hyperloop from an operational perspective by developing simulation models. We consider the Hyperloop system that is expected to be established between Los Angeles and San Francisco, and the demand for this emerging service is estimated by considering the on-road and flight travels made between these two metropolitan cities. We developed a Define, Measure, Analyze, Design, and Verify (DMADV) approach for (a) conceptualizing the problem and understanding the Hyperloop network operations, (b) gathering data from various sources, (c) developing the simulation model, and (d) obtaining the results and proposing managerial insights for efficient network operation. Sensitivity analysis is performed by varying parameters such as the pod capacity, the number of Hyperloop capsules in the system, commuter volume variability and willingness to use Hyperloop rate, and their impact on the performance measures is studied. Results indicate that the number of Hyperloop pods in the system and the commuter volume variability appear to impact the measures exponentially, and hence intense market research on these parameters is recommended. The proposed simulation model developed under the DMADV approach can be used as a recommender tool by any logistics company that is interested in venturing into the Hyperloop market. Highlights: Hyperloop aims to transport passengers between metropolitan cities at a high speed This research is the first to study the Hyperloop from an operational perspective We developed a Define, Measure, Analyze, Design, and Verify approach Simulation model is proposed to analyze the process and suggest recommendations The proposed model can be used as a decision support tool by any logistics company